The Role of the Mosque Institution in Promoting Mental Health and Achieving Behavioral Balance among Youth - Mehdaoui , Dine (Journal of Science and Knowledge Horizons, 2025)
This article explores the intersection of mental health practice and the mosque as spiritual and educational life. The aim is to find out how regular attendance at the mosque contributes to the development of personal behavior and the promotion of mental equilibrium—generally not requiring the help of expert psychological intervention. The study is based on the belief that Islamic teachings and principles have the ability to offer the foundation for the development of the entire person. Though the field of Islamic psychology remains in its nascent stage and much is unexploited, the potential for research here becomes increasingly obvious. It has a concrete application towards prevention and healing of various forms of deviant behavior. This is especially relevant in what has been termed the age of anxiety and psychic distress—a period of growing rates of depression, suicide, and affective disorders. The majority of these issues have their origin in spiritual bankruptcy and an inability to meet inner, spiritual needs within modern definitions of human development. Through its investigation, the article reaches the conclusion that the mosque plays a quiet but potent role in enhancing mental health. It supports attempts at treating deviant behavior by way of prevention, education, and spiritual guidance. Moreover, this role is not monolithic; it collaborates with educational and social institutions for the creation of a balanced and inclusive mental health care system.